PKM Pembinaan dan Pendampingan Sustainability Reporting bagi UMKM Bakery di Surabaya - Yulius Hari; Melvie Paramitha; Minny Elisa Yanggah; Elisa Churota'ayun (Universitas Nurul Jadid, 2023)
Sustainable Development Goals (SDGs) is a global action agreed by world leaders, including Indonesia, to end poverty, reduce inequality and protect the environment. SDGs aim to balance the 3Ps in business activities, namely planet, people, profit. With the balance of the 3Ps, it is expected to realize sustainability or business sustainability. Business sustainability is the dream of all entrepreneurs. The Global Reporting Initiative (GRI) is the most widely used sustainability reporting standard globally, providing comprehensive reporting guidelines for various business sectors. Indonesian SMEs go International! By making sustainability reporting in SMEs, it is hoped that it can improve the reputation of SMEs and support SMEs to go international. This community service activity was carried out with SME partner Bakery Glory in Surabaya in collaboration with the Melati Nusantara activity series. With the aim of accelerating the understanding of sustainable production to develop the potential of SMEs so that their products can be accepted in the international market.